2022
DOI: 10.1038/s41467-022-29502-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulated interaction of ID2 with the anaphase-promoting complex links progression through mitosis with reactivation of cell-type-specific transcription

Abstract: Tissue-specific transcriptional activity is silenced in mitotic cells but it remains unclear whether the mitotic regulatory machinery interacts with tissue-specific transcriptional programs. We show that such cross-talk involves the controlled interaction between core subunits of the anaphase-promoting complex (APC) and the ID2 substrate. The N-terminus of ID2 is independently and structurally compatible with a pocket composed of core APC/C subunits that may optimally orient ID2 onto the APCCDH1 complex. Phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Meiosis is a necessary process in germline development, when paternal and maternal chromosomes undergo synapsis and recombination of the genome prior to producing haploid gametes [ 1 ]. During this process, diploid cells enter to the prophase of meiosis I, including leptotene, zygotene, pachytene, diplotene and diakinesis, to reach the meiotic divisions [ 2 ]. At the early pachytene stage of the male mammals, homologous autosomes are fully synapsed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meiosis is a necessary process in germline development, when paternal and maternal chromosomes undergo synapsis and recombination of the genome prior to producing haploid gametes [ 1 ]. During this process, diploid cells enter to the prophase of meiosis I, including leptotene, zygotene, pachytene, diplotene and diakinesis, to reach the meiotic divisions [ 2 ]. At the early pachytene stage of the male mammals, homologous autosomes are fully synapsed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knocking down PGC1α in these cells promotes a pro-metastatic gene program and enhances metastasis in mice models ( 131 ). PGC1α upregulates the expression of inhibitor of DNA binding protein (ID2), which binds and inhibits a diverse array of bHLH transcription factors ( 136 ). The binding of ID2 suppresses the transcription factor TCF4, resulting in the suppression of metastasis-related genes including integrins, which are known to affect metastasis ( 131 , 137 ).…”
Section: Roles Of Pgc1α In Cancer Cellsmentioning
confidence: 99%
“…22 Furthermore, a recent study indicated that ID2 interacts with the anaphase-promoting complex to activate cell-specific transcription. 23 Despite these important findings, the functional role of ID2 in meiosis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been proposed that the pachytene arrest caused by Ovol1 deletion in mouse testes is due to the increased expression of Id2 22 . Furthermore, a recent study indicated that ID2 interacts with the anaphase‐promoting complex to activate cell‐specific transcription 23 . Despite these important findings, the functional role of ID2 in meiosis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%